Pediatric Nonvariceal Gastrointestinal Hemorrhage - Monroe, Eric J.; Slowik, Voytek; Shin, David S. (Digestive Disease Interventions, 2018)
Gastrointestinal bleeding (GIB) is a relatively rare yet potentially life-threatening event in children. While mesenteric angiography for GIB has grown into a ubiquitous component of adult interventional radiology practice, the pediatric experience is comparatively limited. We herein review the common etiologies and management of GIB in children, with special attention to angiographic technique relevant to pediatric anatomy.
Keywords: pediatric; angiography; mesenteric